IDENTIFIKASI ASAM LEMAK OMEGA PADA ASI EKSKLUSIF MENGGUNAKAN KROMATOGRAFI GC-MS - Titin Aryani; Fitria Siswi Utami; Sulistyaningsih Sulistyaningsih (Universitas 'Aisyiyah Yogyakarta, 2017)
Abstract: Quantitative research aims to identify the omega fatty acids in exclusive breast milk (ASI) Exclusive. The data analysis used data chromatogram Gas Chromatography-Mass Spectrometry (GC-MS). The data generated is breast milk (ASI) had higher levels of omega-3 fatty acids amounting to 28.24%, omega-6 and omega of 0.57% 9 at 26.56%. The conclusion from this study is there is the content of omega-3, omega-6, omega-9 fatty acids in breast milk (ASI). Highest levels of omega fatty acids in breast milk is the omega-3 fatty acid that is equal to 28.24%.Keywords: milk, omega fatty acids, GC-MS